Integration of H2V3O8 nanowires and a GaN thin film for self-powered UV photodetectors. Issue 61 (11th July 2022) - Dou, Yi; Liang, Yujun; Li, Haoran; Xue, Yali; Ye, Hanlin; Han, Yongsheng
Abstract : A self-powered ultraviolet (UV) photodetector was successfully constructed through combining H2 V3 O8 nanowires (NWs) and a GaN thin film. Abstract : H2 V3 O8 /GaN n–n heterojunction ultraviolet photodetectors are fabricated via a facile dip-coating method. The Schottky junction between the GaN and H2 V3 O8 builds a built-in electric field to achieve the self-powered phenomenon. The photodetector presents a high photocurrent (0.23 μA) and a fast response speed (less than 0.3 s) at 0 V bias and under 365 nm light illumination (24.50 mW cm −2 ). Furthermore, the photocurrent increases steadily as the light intensity increases from 0.53 to 24.50 mW cm −2 . The H2 V3 O8 /GaN heterojunction holds great potential to realize high-performance hybrid PDs.